Political Communications of The Ministry of Education and Culture about â€œMerdeka Belajar, Kampus Merdeka (Independent Learning, Independent Campus)â€ Policy: Effective? - Purike, Era (EduLine: Journal of Education and Learning Innovation, 2021)
The policy of the Ministry of Education and Culture (Kemdikbud) regarding â€œMerdeka Belajar, Kampus Merdeka (Free Learning, Independent Campus) as outlined in 5 (five) policies (Permendikbud) as a legal umbrella for this policy. This policy was launched on January 24, 2020 and is a breakthrough made by the Ministry of Education and Culture in the education sector in Indonesia. As a new policy, this policy is likely to experience obstacles, especially in its implementation. Therefore, effective communication is needed to achieve the objectives (outputs) of this policy. This research was conducted through literature review and monitoring of official online media as tools used by the Ministry of Education and Culture to socialize this policy. Policy communication could be effective if: (1) the policy can be received and understood as intended by the government; (2) the policy launched by the government can be approved by the recipient and followed up with the proper implementation as required by the government; (3) there are no significant obstacles to follow up and implement the policy. The results of this study indicate that there are still misinterpretations regarding the contents of this policy. The results of literature review state that educational institutions are still having difficulty implementing this policy in curriculum adjustments and learning activities. They also have obstacles to follow up on links and match programs for independent learning with industry due to it requires much budget and many universities have low budget.